Dynamic model of Ibn Khaldun theory on poverty: Empirical analysis on poverty in majority and minority Muslim populations after the financial crisis. Issue 2 (2014) - ,; ,
Abstract : Purpose – The purpose of this study is to examine the poverty rate of Indonesia, Malaysia and Pakistan representing majority Muslim populations and that of India as a minority Muslim population according to Ibn Khaldun's dynamic model on poverty.Design/methodology/approach – According to Ibn Khaldun, poverty is not merely influenced by economic dimensions. He initiated fundamental factors, as mentioned in his formula, which are the functions of Wealth of the Nation, Government, Human Resource, Shariah, Growth and Justice. This study generates secondary data covering the period from 2000 to 2010 or after the financial crisis of 1997. These data were generated using the Panel method.Findings – The findings of this study reveal that the dynamic model of Ibn Khaldun significantly influenced the level of poverty in Indonesia as a Muslim‐majority population, whereas in Pakistan, only the human development index variable has a significant influence. Meanwhile, like Malaysia, in India, the dynamic model of Ibn Khaldun did not have significant influence.Research limitations/implications – Each country has certain characteristics and background with respect to economic growth, government policy and population that might influence poverty. As a result, the application of Ibn Khaldun's model varies accordingly.Practical implications – The findings reveal that quite a few challenges lie ahead in applying Ibn Khaldun's model in these countries. This needs to be taken on promptly by each country, especially Muslim countries.Originality/Value – This paper is one of the few studies which use Ibn Khaldun' theory on poverty using panel data to investigate the appropriateness of the model.